Tinjauan Fiqih Muamalah terhadap Praktik Jual Beli Tahu dan Tempe di Pasar Ciroyom Bandung - Hilman Baihaqqi; Zia Firdaus Nuzula (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Fikih Muamalah is the laws of Islamic syara' which regulates the relationship between humans in the field of economic activity, one of those is in buy and sell. One of the business activities is the sale and purchase of tofu and tempeh at Pasar Ciroyom Bandung, traders replace unsold tempeh packaging with banana leaf wrappers, mix old tofu with new tofu and make tofu brands such as tofu